Characteristics and Categories of Risk in the Small Enterprises - Anna Bera (Contemporary Economics)
In this article risk typology in a small enterprise has been presented. In the aspect of a small enterprise’s characteristic features that have been synthetically described, the author has tried to define the crux and position of individual risk types in the operation of small market entities. In economy practice, identification and risk management conduct of risk categorization facilitates.